2022
DOI: 10.2169/internalmedicine.9513-22
|View full text |Cite
|
Sign up to set email alerts
|

Successful Elimination of SARS-CoV-2 Following Vaccination with BNT162b2 after Prolonged Viral Infection in an Immunocompromised Lymphoma Patient

Abstract: A 52-year-old man with mantle cell lymphoma treated with bendamustine and rituximab developed prolonged severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Despite elevated titers of anti-spike IgG antibody, protracted pancytopenia persisted for more than six months. Finally, the anti-SARS CoV-2 vaccine, BNT162b2, was administered, which improved his blood cell count and eliminated the virus. The increased anti-spike IgG titer and lymphocyte count after vaccination suggested that both humor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Similar successful viral clearance has been reported in immunodeficiency-associated patients with relapsing or prolonged COVID-19 (13,21). Previously, we treated a case of malignant lymphoma with an anti-CD20mAb-containing regimen, in which SARS-CoV-2 viral shedding persisted for as long as 246 days after the disease onset (8). In the present case, the patient was vaccinated, and the level of anti-SARS-CoV-2 IgG increased to more than 10,000 AU/mL at approximately 3 months after the onset, with the viruses ultimately eliminated.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Similar successful viral clearance has been reported in immunodeficiency-associated patients with relapsing or prolonged COVID-19 (13,21). Previously, we treated a case of malignant lymphoma with an anti-CD20mAb-containing regimen, in which SARS-CoV-2 viral shedding persisted for as long as 246 days after the disease onset (8). In the present case, the patient was vaccinated, and the level of anti-SARS-CoV-2 IgG increased to more than 10,000 AU/mL at approximately 3 months after the onset, with the viruses ultimately eliminated.…”
Section: Discussionsupporting
confidence: 70%
“…We previously showed that patients with hema-tological diseases are less likely to develop antibodies against SARS-CoV-2 than are those with non-hematological diseases (7). Prolonged viral shedding in patients with B-cell depletion caused by anti-CD20mAb has been demonstrated, and prolonged COVID-19 pneumonia during anti-CD20mAb treatment has also been reported (8)(9)(10).…”
Section: Introductionmentioning
confidence: 98%
“…A previous study including patients with lymphoma and a diagnosis of SARS-CoV-2 identified bendamustine exposure, active hematological disease, and comorbidity as prognostic factors for mortality [ 27 ]. Other studies have suggested that bendamustine exposure is a risk factor for patients with prolonged COVID-19 infection [ 28 , 29 ]. In the present study, we also showed that prior bendamustine therapy was a risk factor for COVID-19–related mortality.…”
Section: Discussionmentioning
confidence: 99%